2021
DOI: 10.1371/journal.pone.0250133
|View full text |Cite
|
Sign up to set email alerts
|

Antibody activities in hyperimmune plasma against the Rhodococcus equi virulence -associated protein A or poly-N-acetyl glucosamine are associated with protection of foals against rhodococcal pneumonia

Abstract: The efficacy of transfusion with hyperimmune plasma (HIP) for preventing pneumonia caused by Rhodococcus equi remains ill-defined. Quarter Horse foals at 2 large breeding farms were randomly assigned to be transfused with 2 L of HIP from adult donors hyperimmunized either with R. equi (RE HIP) or a conjugate vaccine eliciting antibody to the surface polysaccharide β-1→6-poly-N-acetyl glucosamine (PNAG HIP) within 24 hours of birth. Antibody activities against PNAG and the rhodococcal virulence-associated prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Results showed that the odds of pneumonia were significantly higher for foals transfused with RE hyperimmune plasma that had lower antibody activity against VapA and and for foals transfused with PNAG hyperimmune plasma that had either lower activity of PNAG or less deposition of complement component 1q (C 0 1q) onto PNAG. 55 The role of the relative or absolute amount of IgG sub-isotype(s) recognising R. equi antigens in the efficacy of RE hyperimmune plasma is unknown. Conflicting evidence exists regarding the association of IgG sub-isotypes with R. equi infection.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Results showed that the odds of pneumonia were significantly higher for foals transfused with RE hyperimmune plasma that had lower antibody activity against VapA and and for foals transfused with PNAG hyperimmune plasma that had either lower activity of PNAG or less deposition of complement component 1q (C 0 1q) onto PNAG. 55 The role of the relative or absolute amount of IgG sub-isotype(s) recognising R. equi antigens in the efficacy of RE hyperimmune plasma is unknown. Conflicting evidence exists regarding the association of IgG sub-isotypes with R. equi infection.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Although several studies 8,40,41,48,55,66,67,75 indicate that transfusion of hyperimmune plasma to foals at age ≤ 24 h is safe, inherent risks associated with plasma transfusion including hypersensitivity reactions, [93][94][95][96] transfusion-related lung injury (TRALI), [97][98][99][100] transfusionassociated circulatory overload (TACO), 100 virus transmission, 101,102 intravenous catheterisation of foals, and handling foals. In a retrospective study reporting the incidence of transfusion reactions between 2003 and 2005 of 107 client-owned horses referred to the University of Wisconsin teaching hospital transfused with plasma, 6% (6/107) of horses had an adverse reaction and all were in foals <7 days of age.…”
Section: Risks Of Hyperimmune Plasma Transfusionmentioning
confidence: 99%
See 3 more Smart Citations